On certain functions of 'a-chung in early Tibetan transcriptional texts - Coblin, W. South (2024)
It is probably fair to say that there is currently considerable consensus among tibetologists on the graphic functions and even on the original phonetic values of the sounds represented by most of the letters of the Tibetan alphabet. An exception to this is the letter r; 'a, now often referred to as `a-chung.